Measuring Outcomes of Continuing Professional Education - Jenny Gough; Peteris Darzinsm; David Beckett (Adult Education Research Conference, 2000)
Continuing professional education (CPE) should improve performance, yet ways of establishing evidence of improvement are hard to identify. We propose a systematic review of the outcomes of various CPE strategies. To do this we need to establish how the effectiveness of CPE can be measured and explore this in the health-care professions.